2019
DOI: 10.1038/s41380-019-0516-z
|View full text |Cite
|
Sign up to set email alerts
|

A methylation study of long-term depression risk

Abstract: Recurrent and chronic Major Depressive Disorder (MDD) accounts for a substantial part of the disease burden because this course is most prevalent and typically requires long-term treatment. We associated blood DNA methylation profiles from 581 MDD patients at baseline with MDD status 6 years later. A resampling approach showed a highly significant association between methylation profiles in blood at baseline and future disease status (P=2.0×10 −16). Top MWAS results were enriched specific pathways, overlapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 68 publications
0
39
0
Order By: Relevance
“…A recent study of 581 individuals with depressive symptoms used machine learning methods to train a predictor of MDD using DNAm data. They found that MRS could discriminate future MDD disease status with an area under the curve (AUC) of 0.72 [13]. Notably, this study did not use an independent sample to test their MRS and they discriminated between transient and chronic MDD over a 6year period.…”
Section: Introductionmentioning
confidence: 92%
“…A recent study of 581 individuals with depressive symptoms used machine learning methods to train a predictor of MDD using DNAm data. They found that MRS could discriminate future MDD disease status with an area under the curve (AUC) of 0.72 [13]. Notably, this study did not use an independent sample to test their MRS and they discriminated between transient and chronic MDD over a 6year period.…”
Section: Introductionmentioning
confidence: 92%
“…Recent epigenome-wide association studies (EWAS) showed an association of wholeblood DNA methylation levels with depressive symptoms 7,8 as well as MDD [9][10][11] , but little is known about brain epigenetic markers of depression or MDD. The EWAS of depressive symptoms were both conducted in late middle-aged and elderly people from the general population (mean age 70 years 8 and 65 years 7 ), an age group with an increased risk of developing dementia 12 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recent EWAS of MDD were performed in younger participants (mean age 42 years) [9][10][11] and it is unclear if their findings can be generalized across age groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have also shown the potential of a DNAm-based risk score to predict MDD and its associated lifestyle and environmental factors, including antidepressant use (14,15). Barbu et al (2020) (15) trained a DNAm predictor of MDD in 3,047 individuals using a penalised regression model and showed that it was significantly associated with self-reported antidepressant use in an independent cohort.…”
Section: Introductionmentioning
confidence: 99%